POTRET PELAKSANAAN SUHBAT USTADZ DAN TILUZ ZAMIN DALAM PEMBELAJARAN BAHASA ARAB DARING - Noor, Fatwiah; Muradi, Ahmad; Syarif, Jamal; Hakim, Arif Rahman (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2022)
The pandemic has affected various aspects of life, including the field of education by implementing online learning. Limited time and communication between teachers and students in the learning process provide different conditions. This is inversely to the terms proposed by Imam Shafi'i for seeking knowledge. He said there are 6 terms, namely Dzaka', Hirsh, Ijtihad, Bulghah, Suhbat Ustadz and TuÌ„luz Zaman. The purpose of this paper is to present the concept of Suhbat Ustadz and TuÌ„luz Zaman in online learning at UPB. This paper conveys a quantitative approach with a descriptive qualitative method. Data obtained from the results of a survey from students and teachers. The results show that the concept of Suhbat Ustadz can be seen from the use of teleconference media and other communicative media. While the concept of tuÌ„luz zaman can be seen from the unlimited learning time or the availability of time outside of lecture hours.